Grapevine rootstock effects on scion sap phenolic levels, resistance to Xylella fastidiosa infection, and progression of Pierce's disease - Wallis, Christopher M.; Wallingford, Anna K.; Chen, Jianchi (Frontiers in Plant Science, 2013)
The xylem-limited bacterium Xylella fastidiosa (Xf) causes Pierce’s disease (PD), an important disease of grapevine, Vitis vinifera L.. Grapevine rootstocks were developed to provide increased resistance to root disease, but rootstock effects on cane and vine diseases remain unclear. Grapevines that consisted of Cabernet Sauvignon or Chardonnay grafted to 13 different rootstocks were inoculated with Xf and evaluated for PD severity and Xf titer after six months. A subset of six rootstock/scion combinations had xylem sap phenolic levels assessed in non-infected and Xf-infected grapevines. Vigor also was analyzed by measuring root lengths and masses. Cabernet Sauvignon grafted to 101-14MG, 1103P, 420A, or Schwarzmann had reduced PD severity compared to Cabernet Sauvignon grafted to 110R, 5BB, or SO4. Chardonnay grafted to Salt Creek or Freedom had reduced PD severity compared to Chardonnay grafted to RS3 or Schwarzmann. Chardonnay grafted to RS3 had greater Xf titer than Chardonnay grafted to 101-14MG, Freedom, or Salt Creek. No other differences in Xf titer among rootstocks were observed. Of the six scion/rootstock combinations which had xylem sap phenolics analyzed, Chardonnay/ RS3 had the highest levels of most phenolics whereas Cabernet Sauvignon/101-14MG had the lowest phenolic levels. However, Chardonnay/101-14MG, which had mild PD symptoms, had greater sap levels of caftaric acid than other scion/rootstock combinations. Sap levels of caftaric acid, methyl salicylate, a procyanidin trimer, and quinic acid were greater in Xf-infected versus non-infected grapevines. Chardonnay on 101-14MG or Salt Creek had greater root mass than Chardonnay on RS3. Cabernet Sauvignon on 101-14MG had greater root mass than Cabernet Sauvignon on 110R. These results identified rootstocks with the capacity for reducing PD symptom progression. Rootstocks also were shown to affect Xf titer, xylem sap phenolic levels, and plant vigor.